2018
DOI: 10.1002/aqc.2921
|View full text |Cite
|
Sign up to set email alerts
|

Native predators control the population of an invasive crab in no‐take marine protected areas

Abstract: 1. The resistance of an ecosystem to species invasion is considered to be related to the abundance and diversity of native species (i.e. biotic resistance hypothesis).Theory predicts that the high native diversity in pristine systems can hinder the establishment and/or the spread of non-native species through direct and indirect mechanisms (e.g. through competitive and/or predatory interactions).2. Here we tested whether predation provides higher resistance to invasion by the Percnidae crab Percnon gibbesi (H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, despite its wide distribution in Mediterranean, there is little knowledge about its trophic relationships with potential predators. Up to date, only Tiralongo et al (2021) directly observed the predation by Gobius paganellus (Gobiidae) on juvenile individuals of P. gibbesi, whereas Noè et al (2018) demonstrated that in marine protected areas the higher diversity and abundance of native predator assemblages directly affect the invasion success of this crab. It is therefore of relevant importance to understand what other predators can contribute to the biological control of this species.…”
Section: Evidence Of Predation On the Invasive Crab Percnon Gibbesi (...mentioning
confidence: 99%
“…However, despite its wide distribution in Mediterranean, there is little knowledge about its trophic relationships with potential predators. Up to date, only Tiralongo et al (2021) directly observed the predation by Gobius paganellus (Gobiidae) on juvenile individuals of P. gibbesi, whereas Noè et al (2018) demonstrated that in marine protected areas the higher diversity and abundance of native predator assemblages directly affect the invasion success of this crab. It is therefore of relevant importance to understand what other predators can contribute to the biological control of this species.…”
Section: Evidence Of Predation On the Invasive Crab Percnon Gibbesi (...mentioning
confidence: 99%